IMPROVEMENT OF THE COMPOSITION OF NONSTICK COLORS - O. S. Komarov; B. M. Nemenjonok; E. V. Rozenberg; T. D. Komarova (Литьë и металлургия, 2016)
The possibility of increasing the hardness (strength) nonburning-on coatings based on distensilimonita and lingosulfanata as binding by the addition of sodium aluminate and polyethylene glycol (PEG-200) was usearched. It was found that addition of these substances enhances strength for the first one temperature ranges 130–1200 ºC, and for the second one – only after drying.It is shown that for distensilimonita zircon (ZrSiO4) these substances provide high strength and as separate binders. But for paints based on Al2O3 their use is not efficient.